2005
DOI: 10.1152/ajpendo.00159.2005
|View full text |Cite
|
Sign up to set email alerts
|

Is insulin an anabolic agent in bone? Dissecting the diabetic bone for clues

Abstract: Diabetic osteoporosis is increasingly recognized as a significant comorbidity of type 1 diabetes mellitus. In contrast, type 2 diabetes mellitus is more commonly associated with modest increases in bone mineral density for age. Despite this dichotomy, clinical, in vivo, and in vitro data uniformly support the concept that new bone formation as well as bone microarchitectural integrity are altered in the diabetic state, leading to an increased risk for fragility fracture and inadequate bone regeneration followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
338
4
30

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(385 citation statements)
references
References 143 publications
(117 reference statements)
13
338
4
30
Order By: Relevance
“…The beneficial roles of insulin on skeletal health has been entertained by many authors [1], supported by the observations that lower BMD in type 1 diabetes [2,3] and higher BMD in subjects with type 2 diabetes [4,5]. We found that there are stronger associations of BMAD with fasting insulin and insulin AUC in AA adolescents.…”
Section: Discussionsupporting
confidence: 85%
“…The beneficial roles of insulin on skeletal health has been entertained by many authors [1], supported by the observations that lower BMD in type 1 diabetes [2,3] and higher BMD in subjects with type 2 diabetes [4,5]. We found that there are stronger associations of BMAD with fasting insulin and insulin AUC in AA adolescents.…”
Section: Discussionsupporting
confidence: 85%
“…Hyperglycemia leads to osteopenia and impairment of wound healing, which is intimately associated with unbalance between the production and the metabolism of reactive oxygen species (ROS) 3 . Also, hyperglycemia can increase the inflammatory response and the osteoclastic activity, which can compromise the bone neoformation during bone repair 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Resorption events have been linked to numerous factors other than cytokines and hormones, such as growth factors and reactive oxygen species (ROS) formation either in the bone microenvironment or in the osteoclastic precursors of the monocyte-macrophage lineage (Bai et al, 2004;Thrailkill et al, 2005b). Over the last decade, evidence has accumulated of ROS participation in bone resorption, with a direct contribution of osteoclasts generating high concentrations of superoxide anion (O2-) and hydrogen peroxide (H2O2) (Muthusami et al, 2005;Bai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%